2021
DOI: 10.1002/onco.13780
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Real-World Data to Investigate the Impact of Race and Ethnicity on Response to Programmed Cell Death-1 and Programmed Cell Death-Ligand 1 Inhibitors in Advanced Non-Small Cell Lung Cancers

Abstract: Background. Racial disparities among clinical trial participants present a challenge to assess whether trial results can be generalized into patients representing diverse races and ethnicities. The objective of this study is to evaluate the impact of race and ethnicity on treatment response in advanced non-small cell lung cancer (aNSCLC) patients treated with PD-1 or PD-L1 inhibitors through analysis of real-world data (RWD). Materials and Methods. A retrospective cohort study of 11,138 lung cancer patients tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 35 publications
1
32
0
Order By: Relevance
“…Illustrated by Figure 8 , a significant discrepancy was found among the five subgroups ( P = .02). The pooled incidence of HPD was 16.2% in patients suffering from gastrointestinal (GI) tract cancer ( n = 5, 95% CI, 10.4%–24.1%) ( 33 , 45 , 56 , 57 , 60 ); 14.4% in patients with NSCLC ( n = 14, 95% CI, 12.2%–17.0%) ( 13 , 16 , 17 , 21 , 29 , 34 , 42 44 , 51 , 54 , 59 , 62 , 63 ), 9.9% in patients with melanoma ( n = 3, 95% CI, 1.6%–43.4%) ( 35 , 36 , 53 ); 10.8% in patients with HCC ( n = 4, 95% CI, 8.4%–13.8%) ( 14 , 39 , 40 , 61 ); 18.06% in patients with HNC ( n = 6, 95% CI, 15.0%–21.6%) ( 15 , 37 , 38 , 48 , 49 , 52 ). Significant differences were found between these five tumor types (Q = 11.16, P = .0248), indicating that tumor type is a source of heterogeneity.…”
Section: Resultsmentioning
confidence: 99%
“…Illustrated by Figure 8 , a significant discrepancy was found among the five subgroups ( P = .02). The pooled incidence of HPD was 16.2% in patients suffering from gastrointestinal (GI) tract cancer ( n = 5, 95% CI, 10.4%–24.1%) ( 33 , 45 , 56 , 57 , 60 ); 14.4% in patients with NSCLC ( n = 14, 95% CI, 12.2%–17.0%) ( 13 , 16 , 17 , 21 , 29 , 34 , 42 44 , 51 , 54 , 59 , 62 , 63 ), 9.9% in patients with melanoma ( n = 3, 95% CI, 1.6%–43.4%) ( 35 , 36 , 53 ); 10.8% in patients with HCC ( n = 4, 95% CI, 8.4%–13.8%) ( 14 , 39 , 40 , 61 ); 18.06% in patients with HNC ( n = 6, 95% CI, 15.0%–21.6%) ( 15 , 37 , 38 , 48 , 49 , 52 ). Significant differences were found between these five tumor types (Q = 11.16, P = .0248), indicating that tumor type is a source of heterogeneity.…”
Section: Resultsmentioning
confidence: 99%
“…Our finding corroborates those of earlier studies demonstrating ethnic differences observed in patients treated with anti-PD-1 monotherapy for advanced non-small cell lung cancer. 51 Interestingly, this association of ethnicity and clinical benefit did not hold in acral, mucosal and uveal melanomas. This observation contradicts the prevailing notion that associations between the efficacy of PD-1 blockade and ethnicity are due solely to differences in the prevalences of melanoma subtypes.…”
Section: Discussionmentioning
confidence: 99%
“…From our perspective, the development of new hallmarks for predicting responses to immunotherapy must take into account the unique immunogenomic features that Asian and Western patients do not share ( 39 , 40 ). As immune checkpoint inhibitors play an increasingly critical role in the treatment of multiple advanced cancers, the correlation between geographic locality and treatment responses warrants further investigations ( 41 ).…”
Section: Discussionmentioning
confidence: 99%